Weed control modifies Tuber melanosporum mycelial expansion in young oak plantations (ANNALS OF FOREST SCIENCE, 2014)
Black truffle (Tuber melanosporum) cultivation is a promising agro-forestry alternative for Mediterranean rural areas, but adequate weed control at seedling establishment still remains a challenge in black truffle plantations. The aim of this study is to evaluate the effects of several weed control strategies on early development of Quercus ilex seedlings and the symbiotic T. melanosporum. In a young black truffle-inoculated holm oak plantation, we assessed for 3 years the effects of two types of mechanical weed control and five mulches in a young Q. ilex plantation inoculated with T. melanosporum. Herbaceous cover, seedling growth and abundance of T. melanosporum mycelium, based on PCR analysis of soil DNA extracts using T. melanosporum-specific primers, were estimated to determine the effectiveness of these treatments in controlling weeds and supporting the growth of both the host tree and the target fungus. The amount of T. melanosporum mycelium in the soil 30 cm around the seedlings was larger under double-layer white mulch than in the rest of treatments tested. Under the white colour mulches, which had the largest light reflection, we registered the cooler soil temperature, and the best weed control was observed on the single- and double-layer black truffles and double-layer white mulch. The effects of double-layer white mulch on herbaceous cover, soil temperature, reflected light, and the expansion of T. melanosporum bring us closer to being able to substitute traditional tilling of truffle orchards for the less expensive mulching treatments.